2002
DOI: 10.1111/j.1467-842x.2002.tb00900.x
|View full text |Cite
|
Sign up to set email alerts
|

The Risks of Everyday Life: Fat content of chips, quality of frying fat and deep‐frying practices in New Zealand fast food outlets

Abstract: Objectives: To collect baseline data on the fat content of hot chips, quality beliefs in fast food outlets throughout New Zealand.• Compare chain and independent outlets.• Identify the key determinants of fat content of chips and quality of cooking fat.• Identify opportunities for action to reduce the fat content of hot chips and improve the fat quality of the frying fat. Methods SampleFast food outlets were randomly selected from a list of all takeaways and unlicensed restaurants listed in the Ne w Zealand Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Clearly many changes can improve the quality of fast food chains, ranging from shifting the temperature of cooking French fries to lower the fat content , calorie and sodium labelling, and portion‐size pricing. One of the most important is to require chains with six or more fast food restaurants to label calories and require pricing such that each calorie of a given food or beverage is charged the exact same amount.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Clearly many changes can improve the quality of fast food chains, ranging from shifting the temperature of cooking French fries to lower the fat content , calorie and sodium labelling, and portion‐size pricing. One of the most important is to require chains with six or more fast food restaurants to label calories and require pricing such that each calorie of a given food or beverage is charged the exact same amount.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Other interventions for preventing childhood obesity that could be modelled in the same way include: reducing food marketing that targets young children (50); reducing the fat content of French fries (51); enhancing access for recreational activities (52); and taxing high fat or sugar products (53,54).…”
Section: Proposed Frameworkmentioning
confidence: 99%
“…Sanny and coauthors (34) found that differences in frying equipment (digitally controlled fryers versus simple frying pans) and frying instructions (oral instructions versus no instructions at all) resulted in considerable differences in frying practices among food handlers in FSEs and to large variations and high acrylamide concentrations in French fries. Various authors have found that the actual frying practices among FSEs can differ considerably (1, 13,25).…”
mentioning
confidence: 99%